2010
DOI: 10.4174/jkss.2010.78.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience of Doppler-Guided Hemorrhoidal Artery Ligation and Rectoanal Repair (DG-HAL & RAR) for the Treatment of Symptomatic Hemorrhoids

Abstract: Purpose: This study is to introduce our preliminary experience of the Doppler-guided hemorrhoidal artery ligation and Rectoanal repair (DG-HAL & RAR) as a new treatment for symptomatic or prolapsed hemorrhoids. Methods: A Doppler probe incorporated proctoscope was inserted under the lithotomy position and the location of the hemorrhoidal artery was identified. The identified artery was ligated as a 'figure of eight' method with an absorbable suture into the submucosa. Then the prolapsed hemorrhoidal pile was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Dearterialization procedures like hemorrhoid artery ligation have a recurrence rate of 5-18% in various studies. [8][9][10][11][12][13][14][15][16][17][18][19] We didn't have long term results in our study but short term results in our study showed that a single treatment can achieve satisfactory results. If the symptoms of bleeding and prolapse due to hemorrhoids are not relieved, further hemorrhoid ligation or other conservative treatment may be tried.…”
Section: Recurrence and Long Term Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] Dearterialization procedures like hemorrhoid artery ligation have a recurrence rate of 5-18% in various studies. [8][9][10][11][12][13][14][15][16][17][18][19] We didn't have long term results in our study but short term results in our study showed that a single treatment can achieve satisfactory results. If the symptoms of bleeding and prolapse due to hemorrhoids are not relieved, further hemorrhoid ligation or other conservative treatment may be tried.…”
Section: Recurrence and Long Term Resultsmentioning
confidence: 84%
“…It has also been shown to be effective in over 90% of cases, with recurrence of 5-18% in different studies. [8][9][10][11][12][13][14][15][16][17][18][19] In a double blind randomized control trial comparing Doppler guided hemorrhoidal artery ligation and mucopexy with simple ligation of hemorrhoids and mucopexy no advantage was found for the Doppler group.…”
Section: Recurrence and Long Term Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 14 patients (14.4%) experienced a recurrence of their preoperative symptoms at the one-year follow-up, and no significant consequences were found. 15 Additionally, Sherif (2016) 18 The clinical and functional outcomes of Dopplerguided (DG) haemorrhoidal artery ligation (HAL) versus traditional haemorrhoidectomy for the treatment of grade III & IV haemorrhoids were studied by Khalil et al in 2019. They claimed that there are no serious risks while utilising DG-HAL, and that any issues are equivalent to those linked to other treatments.…”
Section: Resultsmentioning
confidence: 99%